Reflections on some of the formative years of the British Accounting Review: Thoughts of ducklings and swans. Issue 6 (November 2018) - Gray, Rob; Perks, Bob
Abstract: Between 1978 and 2004 we were engaged in a variety of editorial roles with the British Accounting Review, its forerunner ( The AUTA Review ) and (what became) The British Accounting Review Research Register . This was a period of considerable change for both the journal and the Association. In this short essay, we look back on those 26 years, describing (as we see it) the changes and the reasons for them and indulge in a little reflection on some of the positives and negatives that have flowed around the journal over this period and up to the present.